Equality Before the Law in Law Enforcement in Indonesia - Suhendar; Aringga, Rino Dedi (Yayasan Sinergi Kawula Muda, 2024)
Law enforcement is an effort to uphold and implement the values of justice outlined in formal regulations. However, a significant obstacle often arises from the actions of law enforcement officers conflicting with existing laws. This article discusses law enforcement in Indonesia from the perspective of equality before the law, using a juridical-empirical research method through literature review. The results indicate several deviations in the law enforcement process that hinder the realization of the principle of equality before the law. One of the main causes is the morality of law enforcement officers themselves.